Curved box girder bridges with intermediate diaphragms and supports - Alam, K. M. Ashraful; Lee, Seng Lip; T. Hongladaromp (Bangkok : Asian Institute of Technology, 1972)
The static behavior of simply supported curved box girder bridges with or without intermediate diaphragms subjected to concentrated joint loads is analysed. The analytical model consists of a double cell box section with horizontal annular segmental decks and vertical cylindrical webs. The solutions due to unit vertical and radial loads applied at the jonts for the case without intermediate diaphragms are obtained and used as influence coefficients to derive the solutions for any combination of live loads acting at the joints, as well as to evaluate the effect of intermediate diaphragms. The interactions between the intermediate diaphragm and the box girder are approximated by pairs of vertical and radial reactive forces at the joints only. The values of these reactive forces are determined from the conditions that the rigid body displacements of the intermidiate diaphragm are consistent with the joint displacements under the simultaneous effect of the external loadings and the reactive forces, and that the reactive forces on the diaphragm itself are in equilibrium. Continuous spans over int4ermediate supports provided at the joints are also treated in a similar manner. The numerical results for unit loads applied separately at the midspan and the quarter span for three different radial loading positions, i.e., inner, middle and outer joints, are obtained for the cases without intermediate diaphragm, with diaphragjm at the midspan and with intermediate support at the midspan. The results for the case without intermediate diaphragm are in fact the influence coefficients which are used for the treatment of the other cases. To visualize the influence of intermediate diaphragms and supports, the displacements, the normal force and the bending moments are plotted at differnet sections along the span. The shear forces at the end diaphragms and the reactive forces at the intermediate diaphragms as well as the supports are also shown. A generic concentrated load acting at a joint at the top deck can be resolved into its symmetrical and antisymmetrical components. Dealing with the latter, which greatly simplifies the analysis of the problem and consequently saves computer storage and execution time for its solution, yields practically all the essential details for design purposes. The effect of the symmetrical load component is local and can be either suitably approximated or readily obtained by a similar analysis if more accurate results are desired. This is verified by the general agreement between a finite strip soution for a particular loading and the proposed solution for the antisymmetrical load component. An approximate analysis assuming non-d4eformable cross section is reviewed. The results due to this approximate solution compares poorly with those obtained by the proposed solution for the case without intermediate diaphragms, but are in good qualitative agreement with the case with an intermediate diaphragm at the midspan. Better quantitative agreement can obviously be achieved by the use of more intermediate diaphragms. The stress concentrations in the vicinity of the loads and the diaphragm sections, and the magnitude and distribution of the transverse bending moments which can be predicted accurately by the proposed method should be given careful attention in the design of these bridges. The proposed method of analysis with unit antisymmetrical joint loads is an accurate and efficient means for analysing the behavior of curved box girder bridges with or without intermediate diaphragms and supports. The use of intermediate diaphragms reduces effectively the cross sectional distortion of the bridge, decreases the associated transverse bending moments and increases the rigidity. For the case without intermediate diaphragms, the bridge experiences the maximum distortion when loaded at the inner joint. This distortion is practically eliminated by the addition of a single intermediate diaphragm at the loaded section. For loads acting away form the diaphragm, the effects of the intermediate diaphragm and intermediate support on cross sectional distortion are essentially the same. The use of the intermediate diaphragm reduces the longitudinal bending moments and redistributes the longitudinal normal forces in the vicinity of the diaphragm sections. Without intermediate diaphragms, inner edge loadings are more severe than outer edge loadings, but the reverse is true in presence of intermediate diaphragms. The general response of curved box girder bridges predicted by the proposed solutions agrees well with experimental observations reported elsewhere.
A disssertation submitted in partial fulfillment of the requirements for the degree of Docgtor of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (Ph.D.) - Asian Institute of Technology, 1972
Keywords: Bridges; Girders